The protective role of body appreciation against media-induced body dissatisfaction. (September 2015) - Andrew, Rachel; Tiggemann, Marika; Clark, Levina
Highlights: Body appreciation protects against body dissatisfaction from thin-ideal exposure. Appearance comparison predicts increased body dissatisfaction after media exposure. Appearance comparison does not account for body appreciation's protective role. Use of media protective strategies is positively correlated with body appreciation. Abstract: This study aimed to examine the protective role of positive body image against negative effects produced by viewing thin-idealised media. University women ( N  = 68) completed trait measures of body appreciation and media protective strategies. At a subsequent session, participants viewed 11 thin-ideal advertisements. Body dissatisfaction was assessed before and after advertisement exposure, and state measures of self-objectification, appearance comparison, and media protective strategies were completed. Results indicated that body appreciation predicted less change in body dissatisfaction following exposure, such that participants with low body appreciation experienced increased body dissatisfaction, while those with high body appreciation did not. Although state appearance comparison predicted increased body dissatisfaction, neither state self-objectification nor appearance comparison accounted for body appreciation's protective effect. Trait and state media protective strategies positively correlated with body appreciation, but also did not account for body appreciation's protective effect. The results point to intervention targets and highlight future research directions.